The role of social media In the promotion and use of drugs in juveniles "Field study of juveniles in care centers" (Journal of Namibian Studies : History Politics Culture, 2023)
Drugs This scourge invades the minds of young people, especially the events of them "under the age of eighteen", which usually starts from experience and then addiction.Now that we are in the twenty-first century and in light of the wide range of movement created by social media platforms, there are many dangers that are drugs, as these platforms allow to communicate with a lot of what we know and do not know, Through its silent talk, which is only seen by its owner "by the symbols placed on smartphones" it allows talking in all directions.